Safety, immunogenicity and effect on viral rebound of HTI vaccines combined with a TLR7 agonist in early-treated HIV-1 infection: a randomized, placebo-controlled phase 2a trial - Lucia Bailón; José Moltó; Adrian Curran; Julen Cadiñanos; Juan Carlos Lopez Bernaldo de Quirós; Ignacio de Los Santos; Juan Ambrosioni; Arkaitz Imaz; Susana Benet; Paula Suanzes; Jordi Navarro; Juan González-García; et al. (Nature Communications)
Abstract Building on results from the AELIX-002 trial with HIVACAT T-cell immunogen (HTI)-based vaccines, the AELIX-003 (NCT04364035) trial tested the safety of the combination of ChAdOx1.HTI (C) and MVA.HTI (M), with the TLR7 agonist vesatolimod (VES), in a double-blind, placebo-controlled, randomized clinical trial in 50 virally suppressed early-treated men with HIV-1 infection. Secondary objectives included immunogenicity and effects on viral rebound kinetics during a 24-week antiretroviral treatment interruption (ATI). The most common treatment-related adverse events were mild-to-moderate injection-site pain, influenza-like illness, headache, and fatigue. Strong, broad, and HTI-focused T-cell responses were induced by vaccination. All participants experienced viral rebound in ATI; 33.3% and 23.5% (P = 0.4494) of CCMM + VES and placebo recipients, respectively, remained off antiretroviral therapy for 24 weeks. Post hoc analysis confirmed a correlation between levels of HTI-specific T cells and prolonged time off antiretroviral therapy. The combination of HTI vaccines and VES was safe and elicited robust T-cell responses.